CPR5 modulates salicylic acid and the unfolded protein response to manage tradeoffs between plant growth and stress responses. (3rd February 2017) - Meng, Zhe; Ruberti, Cristina; Gong, Zhizhong; Brandizzi, Federica
Summary: Completion of a plant's life cycle depends on successful prioritization of signaling favoring either growth or defense. Although hormones are pivotal regulators of growth–defense tradeoffs, the underlying signaling mechanisms remain obscure. The unfolded protein response (UPR) is essential for physiological growth as well as management of endoplasmic reticulum (ER) stress in unfavorable growth conditions. The plant UPR transducers are the kinase and ribonuclease IRE1 and the transcription factors bZIP28 and bZIP60. We analyzed management of the tradeoff between growth and ER stress defense by the stress response hormone salicylic acid (SA) and the UPR, which is modulated by SA via unknown mechanisms. We show that the plant growth and stress regulator CPR5, which represses accumulation of SA, favors growth in physiological conditions through inhibition of the SA‐dependent IRE1–bZIP60 arm that antagonizes organ growth; CPR5 also favors growth in stress conditions through repression of ER stress‐induced bZIP28/IRE1–bZIP60 arms. By demonstrating a physical interaction of CPR5 with bZIP60 and bZIP28, we provide mechanistic insights into CPR5‐mediated modulation of UPR signaling. These findings define a critical surveillance strategy for plant growth–ER stress defense tradeoffs based on CPR5 and SA‐modulated UPR signaling, whereby CPR5 acts as a positive modulator of growth in physiological conditions and in stress by antagonizing SA‐dependent growth inhibition through UPR modulation. Significance Statement: Plants must prioritize resources to favor either growth or defense to stresses, but the underlying signaling pathways are largely unknown. Here we show that CPR5, a critical modulator in the salicylic acid pathway, intersects with the unfolded protein response in order to manage the balance between growth and stress defense.